Coloniality of Power in Global Development Teams: Perspective from Indian and Brazilian Tech Workers - Antoine, Sébastien (AoIR Selected Papers of Internet Research, 2026)
The global digitalization process sweeping the world in the last few decades is often approached through the prism of some disruptive or innovative tech products, the big tech companies that “built” them or the relentless public efforts to regulate them. Still, the practical picture actually looks much more mundane: taking the form of products as seemingly as simple as an e-commerce banner, a check-in app or a simple sale receipt, developed in global teams bringing together developers, designers, researchers, quality analysts or products and projects managers often based in the Majority World – in major tech subcontracting or outsourcing hubs such as India or Brazil – and working directly for clients or subsidiaries based in Europe or the US. But who are these workers? And how are the international division of labour, coloniality of power and overall political economy of the tech industry shaping their work experiences and the products they build? Based on an ongoing global research and extensive ethnographic interviews with Brazilian and Indian tech workers regarding their trajectories, worldviews and experience in global teams, this paper aims at uncovering their perspectives on the inner workings of the companies they are working for, the challenges of consultancy work for clients based in the Minority World and the very social, cultural and political implications of this global organization of labour that then become visible.